Трофим Борисов: очерк : [для среднего и старшего школьного возраста] / Семён Шихарев - Шихарев Семен Тарасович (Удмуртия, 1990)
Экземпляры: АБ (20161404) / Инвентарный номер: 24000 / Цена: 0.15 / Сис.шифр: 66.61(2)8 / Авт.знак: Ш 65 / ГРНТИ: 11 / ББК: 66.61(2)8